Innovation Models : Development Of Resources and Learning Materials - Nurcahaya Nurcahaya (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
Education in the future expects changes in learning approaches that focus on individual abilities and prioritize students as the main subject (student centered). Facing the evolution of education during the COVID-19 pandemic and the direction towards Society 5.0, it is necessary to innovate in the development of learning resources and materials, bearing in mind the importance of learning resources and materials in the teaching and learning process. One of the innovative ways to develop learning resources and materials is through the application of the Quizizz-based development method. The hope is that with this approach, students' responses to Quizizz-based teaching materials and resources will be very positive, indicating strong support from students for using this approach in the learning process.